Incumbent Advantage, Voter Information and Vote Buying - Cesi Cruz; Philip Keefer; Julien Labonne (Inter-American Development Bank (IDB), 2016)
Results from a new experiment shed light on the effects of voter information on vote buying and incumbent advantage. The treatment provided voters with information about a major spending program and the proposed allocations and promises of mayoral candidates just prior to municipal elections. It left voters more knowledgeable about candidates' proposed policies and increased the salience of spending, but did not affect vote shares and turnout. Treated voters were more likely to be targeted for vote buying. We develop a model of vote buying that accounts for these results. The information raised voter expectations regarding incumbent performance, especially in incumbent strongholds. Incumbents increased vote buying in response. Consistent with this explanation, both knowledge and vote buying impacts were higher in mu-nicipalities with dominant incumbents. Our findings show that, in a political environment where vote buying is the currency of electoral mobilization, incumbent efforts to increase voter welfare may take the form of greater vote buying.
hdl:11319/7730
Keywords: D72; P16; 330; Political Economy; Vote Buying; Information; Elections